2022
DOI: 10.3389/fonc.2022.935816
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of miRNAs Revealed miR-92b-3p, miR-182-5p and miR-183-5p as Potential Novel Biomarkers in Melanoma-Derived Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are important mediators in the intercellular communication, influencing the function and phenotype of different cell types within the tumor micro-milieu and thus promote tumor progression. Since EVs safely transport packages of proteins, lipids and also nucleic acids such as miRNAs, EVs and their cargo can serve as diagnostic and prognostic markers. Therefore, the aim of this study was to investigate EV embedded miRNAs specific for melanoma, which could serve as potential biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…An early miRNA expression profile showed that miR-92b was among the top thirteen dysregulated miRNAs and it was higher in all astrocytoma grades as compared with normal tumor samples (20). Aberrantly increased levels of miR-92b have also been reported in breast and bladder cancers, and melanoma-derived extracellular vesicles (33)(34)(35) (22,28,36,37). Additionally, stable transfected GBM cells with a vector that knocked down miR-92b reduced the proliferation rate in a subcutaneous GBM mouse model (28).…”
Section: Discussionmentioning
confidence: 97%
“…An early miRNA expression profile showed that miR-92b was among the top thirteen dysregulated miRNAs and it was higher in all astrocytoma grades as compared with normal tumor samples (20). Aberrantly increased levels of miR-92b have also been reported in breast and bladder cancers, and melanoma-derived extracellular vesicles (33)(34)(35) (22,28,36,37). Additionally, stable transfected GBM cells with a vector that knocked down miR-92b reduced the proliferation rate in a subcutaneous GBM mouse model (28).…”
Section: Discussionmentioning
confidence: 97%
“…However, with regard to melanoma, Pfeffer et al ( 36 ) were not able to detect any difference in the plasma levels of hsa-miR-221-3p between melanoma patients and healthy controls. In the serum of melanoma patients, Li et al ( 37 ) identified miR-221 as a predictor of poor outcomes in melanoma patients, but recently other authors did not find significant differences in hsa-miR-221-3p levels in serum between healthy donors and melanoma patients ( 38 ). Similarly, Gasparello et al ( 39 ) found that hsa-miR-221-3p did not discriminate between early CRC patients and healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s discomfort can be reduced using non-invasive technology to collect bodily fluids, separate exosomes for miRNA identification, and determine the type of tumor. Moreover, they can serve as an early detection method in scenarios where pathology and imaging fail to yield valuable insights regarding microtumors ( Gerloff et al, 2022 ; Takizawa et al, 2022 ). Hiroshi and his colleagues demonstrated that matrix miR-21 is more crucial for the progression of GC than tumor cell miR-21 ( Uozaki et al, 2014 ).…”
Section: The Potential Of Caf-derived Exosomal Mirnas In Diagnosis An...mentioning
confidence: 99%